Employees' innovative work behavior and change management phases in government institutions: The mediating role of knowledge sharing - Nawal Abdalla Adam (Administrative Sciences, 2022)
The change management process in government institutions includes many challenges that require identifying the factors that may facilitate such a process. This study aims to examine the mediating impact of knowledge sharing (KS) on the relationship between employees' innovative work behavior (EIWB) and change management phases in governmental institutions, based on Lewin's model. The data were collected from 300 employees working in governmental institutions in Saudi Arabia using a structured survey questionnaire method. Structural equation modeling (SEM-PLS) with bootstrap procedures was used to test the research hypotheses. The results of the study demonstrated that KS has a significant mediating impact on the relationship between EIWB and the stages of change management (unfreezing, change process, and refreezing). Additionally, KS had greater mediating effects on the unfreezing and refreezing phases than on the change process phase. These results indicate the importance of promoting EIWB and encouraging a knowledge sharing culture for the successful implementation of change programs in governmental institutions.
Keywords: 350; change management process; employees' innovative work behavior; governmental institutions; knowledge sharing; Lewin's model